2021
DOI: 10.1177/15234223211057611
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Employees Through a Virtuous Environment! Does Positive Affect Mediate in the Relationship?

Abstract: The Problem The high rate of disengagement among the workforce affects the overall functioning of the organizations as disengaged employees are not only dissatisfied but can also spread negativity among their fellows. Therefore, there is an emerging need to ascertain how organizations can contribute in reducing such disengagement. The Solution Findings from this study suggests that an organizational environment of respect, trust, forgiveness, and care and concern can solve the problem of disengagement. Such an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A few recent studies found that affective well-being is a significant mediator linking organizational virtuousness to affective commitment, work engagement, job performance, and organizational citizenship behaviors (Ahmed et al, 2018 ; Magnier-Watanabe et al, 2017 ; Singh et al, 2018 ). Employees who perceive themselves to be working in a virtuous organization are likely to experience positive emotions (e.g., happy, joyful, pleasant, and contented), and as a result are likely to be committed and engaged at work (Rego et al, 2011 ; Sharma & Goyal, 2021 ). The researchers explained that organizational virtuousness cultivates a sense of flow, engagement, and well-being among employees because of positive emotions from positive social interactions (Rego et al, 2010 ).…”
Section: The Affective Process Of Organizational Virtuousnessmentioning
confidence: 99%
“…A few recent studies found that affective well-being is a significant mediator linking organizational virtuousness to affective commitment, work engagement, job performance, and organizational citizenship behaviors (Ahmed et al, 2018 ; Magnier-Watanabe et al, 2017 ; Singh et al, 2018 ). Employees who perceive themselves to be working in a virtuous organization are likely to experience positive emotions (e.g., happy, joyful, pleasant, and contented), and as a result are likely to be committed and engaged at work (Rego et al, 2011 ; Sharma & Goyal, 2021 ). The researchers explained that organizational virtuousness cultivates a sense of flow, engagement, and well-being among employees because of positive emotions from positive social interactions (Rego et al, 2010 ).…”
Section: The Affective Process Of Organizational Virtuousnessmentioning
confidence: 99%